La imagen de gobernante ideal en las obras de Prudencio - Myazina, Olga (Gerión. Revista de Historia Antigua, 2008)
The purpose of this article is to discover some of the elements of the christian political doctrine in the works of Aurelius Prudentius Clemens; to investigate the creation of the image of the ideal governor in the poem “Against Symmachus”; and to show the originality of his ideas and his contribution to the development of the christian ideology.